Integrated rural development programme in Barizal - Jakariya Caudhuri, A. T. M., 1943- (Integrated Rural Development Programme, Research, Evaluation, and Monitoring Division, 1979)
Survey of the role of the cooperatives in rural development in the district of Barisal; report covers July to December 1977.